What are the effects of irrigation rates and cropping systems on the soybean agronomic traits? - Cruz, Victor Hugo; Tomaz, Rafael Simões; Lima, Ronaldo Cintra (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
The irregularity and uneven distribution of rainfall may restrict the potential productive development of soybeans, causing numerous losses to farmers. The use of irrigation systems in hydrically heterogeneous areas are important measures that should be adopted during the crop cycle. Furthermore, the implementation of conservationist strategies, such as crop rotation or intercropping and no-till (NT) farming systems, can minimize the damage caused by water deficit. Therefore, the present study aimed to evaluate the soybean yield under different irrigation sheets and cropping systems in the extreme west of São Paulo. A completely randomized design was used, with 10 repetitions, in a subdivided plot scheme. The treatments were composed of different cropping systems in the plots, with four levels (conventional system; NT, using Urochloa brizantha  cv Paiaguás; U. brizantha  cv Piatã; and  U. ruziziensis  cv Ruziziensis), and different irrigation scheduling in the subplots, with three levels of irrigation scheduling (0%, 70% and 100%) based on reference evapotranspiration (ETo). Irrigation rates of 70% and 100% ETo in the conventional system provided higher grain yields under the climatic conditions in which the experiment was conducted. However, the continuity of long-term research is necessary, since NT is incipient, and have been implemented only two years ago. This is a relatively short period to observe the advantages of this cultivation system and for its consolidation process. Thus, the Brachiaria residual dry mass showed similar behavior in NT at the irrigation levels evaluated.